Transferrin Receptor 2 Is Frequently and Highly Expressed in Glioblastomas - Calzolari, Alessia (Neoplasia Press Inc., 2010)
Under physiological conditions, transferrin receptor 2 (TfR2) is expressed in the liver and its balance is related to the cell cycle rather than to intracellular iron levels. We recently showed that TfR2 is highly expressed in glioblastoma cell lines. Here, we demonstrate that, in these cells, TfR2 appears to localize in lipid rafts, induces extracellular signal-regulated kinase 1/2 phosphorylation after transferrin binding, and contributes to cell proliferation, as shown by RNA silencing experiments. In vitro hypoxic conditions induce a significant TfR2 up-regulation, suggesting a role in tumor angiogenesis. As assessed by immunohistochemistry, the level of TfR2 expression in astrocytic tumors is related to histologic grade, with the highest expression observed in glioblastomas. The level of TfR2 expression represents a favorable prognostic factor, which is associated with the higher sensitivity to temozolomide of TfR2-positive tumor cells in vitro. The endothelial cells of glioblastoma vasculature also stain for TfR2, whereas those of the normal brain vessels do not. Importantly, TfR2 is expressed by the subpopulation of glioblastoma cells with properties of cancer-initiating cells. TfR2-positive glioblastoma cells retain their TfR2 expression on xenografting in immunodeficient mice. In conclusion, our observations demonstrate that TfR2 is a neoantigen for astrocytomas that seems attractive for developing target therapies.